2015
DOI: 10.1007/s11244-015-0436-3
|View full text |Cite
|
Sign up to set email alerts
|

On the Way to a More Open Porous Network of a Co–Re/Al2O3 Catalyst for Fischer–Tropsch Synthesis: Pore Size and Particle Size Effects on Its Performance

Abstract: Five different c-alumina supports were used, one commercial and four prepared in a macro-mesoporosity range of 7-1000 nm by different preparation methods. A simple method was used to obtain a macromesoporous alumina support by modification of an initial commercial mesoporous alumina with a pore generating agent. Supports were used to prepare Fischer-Tropsch synthesis (FTS) catalysts. Supports and catalysts were characterized by several techniques and tested in a labscale fixed-bed reaction unit in the FTS at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…1). These novel pore structures minimize the mass transfer limitation of reactants during catalyst preparation and reactions, which improves the metal dispersion and the contact frequency between reactants and active sites, leading to improved catalytic performance [20]. Mass transfer limitation is an important factor affecting catalyst performance (activity and hydrocarbon selectivity) in FTS because a CO/H 2 ratio gradient may exist due to the different diffusion rates of CO and H 2 along a long, small pore channel.…”
Section: Introductionmentioning
confidence: 99%
“…1). These novel pore structures minimize the mass transfer limitation of reactants during catalyst preparation and reactions, which improves the metal dispersion and the contact frequency between reactants and active sites, leading to improved catalytic performance [20]. Mass transfer limitation is an important factor affecting catalyst performance (activity and hydrocarbon selectivity) in FTS because a CO/H 2 ratio gradient may exist due to the different diffusion rates of CO and H 2 along a long, small pore channel.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of the diffusion limitations were much lower for the catalyst obtained when the support was modied to add macropores between 100 and 1000 nm. 17 T. Witoon et al also obtained similar results using meso-macroporous silica-supported cobalt catalysts. 18 They found that with large catalyst particles (650 to 850 mm), the C 5+ selectivity of cobalt supported on meso-macroporous silica was much higher than that on unimodal mesoporous silica.…”
Section: Introductionmentioning
confidence: 64%
“…1 [17]. The similarity in the diffractogram indicates that the alumina phase is not considerably influenced by the PS amount [29]. Nevertheless, a slight improvement in crystallinity with increasing PS concentration is observed.…”
Section: X-ray Powder Diffraction (Xrd)mentioning
confidence: 74%